An old absolutist amending clause as the 'new' instrument of delegated legislation. (2nd January 2016) - Pečarič, Mirko
ABSTRACT: This paper deals with the origins of the non-delegation principle of legislative powers, with reasons for withdrawal from a strict conception of this principle and with the nature of delegation that pervades in today's states. The paper points to changes in the constitutional and legal levels that have introduced a form of the so-called Henry VIII clause. Because the Executive can by this clause amend or repeal primary legislation, it was/is in the view of many lawyers unconstitutional, although it appears in the legislation more and more often and it is almost the same as executive orders. This clause cannot be a problem for the constitutional separation of power, if we look at it not as a point of separation but as a division of labour, in the terms of responsible government, where Parliament still controls and approves the operations of the Executive, while additional measures for control from the other stakeholders can also be accepted.